ChemInform Abstract: Synthesis of α‐Di or Trisubstituted (Tetrahydrofuran‐2‐yl)methanols via Photoinduced Additive‐Free Intermolecular Addition of THF to Aromatic Aldehydes or Ketones. Issue 15 (15th April 2014) - Hao, Xinqi; Liu, Chaoli; Liu, Chenli; Chen, Yiyong; Zhao, Xuemei; Song, Maoping; Qian, Rong; Guo, Hao
Abstract The title synthesis provides the target products in only moderate yields.